EVALUASI BERJALAN TERHADAP PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KOTA PADANG - Yofita Sari; Jumiati Jumiati (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
Abstract The complete systematic land registration program (PTSL) is one of the programs to accelerate registration, measurement and mapping of land parcels so that maps of their fields are known and certificates can be given as proof of land ownership rights by the community. This program implementation has been regulated in The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency No.6 of 2018 concerning Complete Systematic Land Registration. The problem in this study is that there are still many lands that have not yet been registered in the city of Padang and do not have land certificates. And the purpose of this study is to find out the implementation of the PTSL Program in the City of Padang and to find out the factors that influence the implementation of the PTSL Program in the City of Padang. This research is a qualitative research with descriptive method, the research was conducted at the National Land Agency (BPN) of Padang City.Determination of research informants by purposive sampling, which is related to the PTSL Program, namely Head of Legal and Land Relations (BPN) Padang City , and the village officials as PTSL executive members and community registrants in the PTSL program in Padang City. This study discusses on going evaluation a program because the program is still being implemented in the City of Padang. So that it refers to the evaluation theory which consists of 6 (six)aspects the effectiveness, efficiency, adequacy, equity, responsiveness and accuracy. The results of the study show how to implement the PTSL program in the city of Padang, this can be seen from several aspects that have not been maximized because there are several problems in the field, such as lack of human resources as executors and the status of customary land which is an obstacle in registering land because many get less approval from their people. Keywords : On going evaluation, The complete systematic land registration program (PTSL) ,land registration, land certificate.